Relevansi Konstitusionalisme dalam Pembentukan Undang-Undang di Indonesia - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Zahrotul Jannah Khoiroh; Revalina Devra Amartya Putri; UIN Raden Mas Said Surakarta (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
Constitusionalism, as a fundamental principle upholding the rule of law and the recognition of fundamental rights of citizens, holds crucial relevance in the formation of laws in Indonesia. The primary objective of constitusionalism in this context is to ensure the alignment of statutory regulations with the noble values enshrined in the 1945 Constitusion of the Replubic of Indonesia (UUD 1945). The legislative process in Indonesia, which is based on the principles of democracy, justice, and respect for human roghts, necessitates contitutionalism as a mtehodological guideline. This research employs a qualitative research method with a literature study apporoach. Through an indepth analysis of various legal and theoretical sources, this study explores how constitutionalism influences the formation of laws, including ensuring the absence of substantive and procedural contradictions with the UUD 1945. Furthermore, this research examines the role of conctitutionakism in regulating the relations between state institutions in the legislative process, strengthening the function of the Constitutional Court in judical review and limiting the potential for abuse of power. Consequently, this research argues that the relevence of constitutionalism the quality of the resulting laws, as well as their implications for the justice and welfare of all Indonesian people.